Depression, anxiety, insomnia, stress, and the way of coping emotions as risk factors for ischemic stroke and their influence on stroke severity: A case–control study in Lebanon - Maalouf, Elise; Hallit, Souheil; Salameh, Pascale; Hosseini, Hassan (Frontiers in Psychiatry, 2023)
Background: Stroke is a leading cause of disability and death worldwide. There are numerous debates regarding the relationship between depression, anxiety, perceived stress, insomnia, and ischemic stroke. Moreover, no research on the efficacy of emotion regulation, which is critical for various components of healthy affective and social adaptability, is being conducted. Hence, our study investigated whether depression, anxiety, stress, insomnia, and emotion regulation may be risk factors for ischemic stroke among Lebanese individuals. Furthermore, we examined the ability of two specific types of emotion regulation (cognitive reappraisal and expressive suppression) to act as possible moderators of the relationship between these mental health issues and the risk of ischemic stroke. Methods: This is a case-control survey study involving 113 Lebanese inpatients with a clinical diagnosis of ischemic stroke admitted in hospitals and rehabilitation centers in Beirut and Mount Lebanon, and 451 age- (within 5 years) and gender-matched volunteers without clinical signs of stroke as controls recruited from the same hospitals as the cases or attending outpatient clinics for illnesses or treatments unconnected to stroke or transient ischemic attack, as well as visitors or relatives of inpatients (April 2020-April 2021). Data was collected by filling out an anonymous paper-based questionnaire. Results: According to the outcomes of the regression model, depression (aOR: 1.232, 95%CI: 1.008-1.506), perceived stress (aOR: 1.690, 95%CI: 1.413-2.022), lower educational level (aOR: 0.335, 95%CI: 0.011-10.579) and being married (aOR: 3.862, 95%CI: 1.509-9.888) were associated with an increased risk of ischemic stroke. The moderation analysis revealed that expressive suppression had a significant moderating effect on the relationship between depression, anxiety, perceived stress, insomnia, and ischemic stroke risk, resulting in an increased risk of stroke incidence. In contrast, cognitive reappraisal significantly reduced the risk of ischemic stroke by moderating the association between ischemic stroke risk and the following independent variables: perceived stress, insomnia. Conclusion: Despite several limitations, the findings of our study suggest that people who are depressed or stressed are more likely to have an ischemic stroke. Moreover, the study shed light on the role of emotion regulation in the relationship between depression, anxiety, perceived stress, insomnia, and ischemic stroke.